2022
DOI: 10.3389/fmicb.2022.833566
|View full text |Cite
|
Sign up to set email alerts
|

Microbe-Mediated Thermotolerance in Plants and Pertinent Mechanisms- A Meta-Analysis and Review

Abstract: Microbial symbionts can mediate plant stress responses by enhancing thermal tolerance, but less attention has been paid to measuring these effects across plant-microbe studies. We performed a meta-analysis of published studies as well as discussed with relevant literature to determine how the symbionts influence plant responses under non-stressed versus thermal-stressed conditions. As compared to non-inoculated plants, inoculated plants had significantly higher biomass and photosynthesis under heat stress cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 197 publications
(222 reference statements)
1
7
0
Order By: Relevance
“…Some studies have shown that AMF can improve contents of osmolytes, such as soluble sugars and proteins, in host plants exposed to Cd or heat stress (Wu, 2011;Dastogeer et al, 2022;Wang et al, 2022a), which was consistent with our results under ET + Cd. The stimulation of G. mosseae on two substances suggested that AMF might improve the osmotic regulation ability of alfalfa against oxidative stress from the coexistence of ET and Cd.…”
Section: Soluble Sugars and Proteins In Alfalfasupporting
confidence: 93%
“…Some studies have shown that AMF can improve contents of osmolytes, such as soluble sugars and proteins, in host plants exposed to Cd or heat stress (Wu, 2011;Dastogeer et al, 2022;Wang et al, 2022a), which was consistent with our results under ET + Cd. The stimulation of G. mosseae on two substances suggested that AMF might improve the osmotic regulation ability of alfalfa against oxidative stress from the coexistence of ET and Cd.…”
Section: Soluble Sugars and Proteins In Alfalfasupporting
confidence: 93%
“…The WSEB isolates from heat T varieties were well established under an increasing temperature range when compared to the heat S variety. The ability of these endophytes might increase the bounds of temperature tolerance of heat T varieties ( Dastogeer et al., 2022 ). This was in line with the studies that growth of spot inoculated purified microbial isolates on medium plates under selection pressure of some chemicals or incubation conditions is considered as tolerant to respective stress condition.…”
Section: Discussionmentioning
confidence: 99%
“…It has been seen that heat stress increases the concentration of amino acids while decreasing the concentration of starch, sugars, and lipids. Maltose concentration has been seen to be elevated ( Dastogeer et al, 2022 ). At the molecular level, heat stress leads to protein denaturation and misfolding.…”
Section: Physiological and Molecular Response Of Phyto-microbiome Aga...mentioning
confidence: 99%